Sustainable blooms: a look at environmental practices in U.S. floriculture - Solliday, Amanda; Langston, Allison; Knuth, Melinda (Frontiers in Sustainability, 2026)
The intensification of environmental issues in recent years, notably climate change, has brought sustainability to the forefront of floriculture business strategy. However, the implementation of sustainable practices is not well-documented at the industry level. To better understand the scope and limitations of sustainable practices among flower growers, wholesalers, retail florists, and floral suppliers in the United States, a nationwide survey was implemented through floriculture professional organizations. Information collected on current and planned sustainability measures revealed differences in implementation and future priority among industry segments, with the results indicating segment-specific needs to achieve sustainability goals. Persistent cost and communication barriers point to opportunities for targeted incentives and improved consumer-facing strategies to support broader adoption of sustainable practices. The findings suggest that sustainability planning is an emerging practice in floriculture, with most existing plans implemented in the past 5 years, which underscores the need for continued educational support and outreach for sustainable strategies within floriculture.